Effect of Copper Amendments on the Quality of Essential Oils Extracted from the Aerial Parts of Mentha arvensis L. Issue 2 (4th March 2021) - Bisht, Mamta; Pande, Chitra; Tewari, Geeta
Abstract: Mentha arvensis L. is one of the highly valued aromatic plants due to its essential oil which finds wide application in food, flavour and pharmaceutical industries. A polyhouse study was conducted to determine the effect of copper on the essential oil composition of M. arvensis L. The amendments of copper were 270, 500, 700 and 900 mg kg −1 in triplicate along with an unamended control. After 90 days, the aerial parts of the plant were harvested, hydrodistilled and analysed by GC and GC-MS. Analysis revealed the presence of thirty-nine compounds of which twenty-two compounds were identified in control representing 96.86 % of the total oils. The main identified components in the oil of plants grown in unamended soil was menthol (84.64 %) along with menthone (4.19 %), iso -menthone (2.23 %), menthyl acetate (1.02 %) and germacrene D (1.10 %) as minor constituents. For the amendments at the level Cu270, Cu500, Cu700, Cu900 mg kg −1 twenty, seventeen, seventeen and seventeen compounds were identified representing 97.80 %, 97.56 %, 96.01 % and 96.96 % of the total extracted oil. The major component in all the oil samples was menthol. The quantitative variation for menthol was found to be highest for the higher level of copper amendments (Cu900 mg kg -1 ) which was 86.41 %, while no much change was observed in the essential oil yield of M. arvensis L. after copper amendments. Thus, aromatic and medicinal plants can be cultivated in the metal-polluted site.